Interactions verbales enseignants-étudiants en cours magistral et compétences transversales des enseignants - Julien Berthaud; Amélie Duguet
In French higher education, the relevance of lectures is regularly a subject of debate, especially with regard to the teaching practices implemented in this teaching environment. While research has repeatedly focused on this type of teaching method, few studies have attempted to describe the interactional practices of teachers during lectures empirically, or to identify the factors that influence these practices. Based on data collected among 276 teachers at a French university, this article aims to describe the nature of these practices but also the links that they have with individual and contextual factors, among which the transversal skills of teachers are considered. Specifically, our results lead to reconsider the idea according to which lectures hinder any form of teacher-students interaction.